2019
DOI: 10.1080/17445647.2019.1685605
|View full text |Cite
|
Sign up to set email alerts
|

Structural geology of Ganymede regional groove systems (60°N–60°S)

Abstract: Brittle deformation on Ganymede surface is represented by grooves tectonic linear landforms. These are regional scale structures that show well-defined morphology from straight to curvilinear. High density of grooves occupies most of the light terrain of the satellite, the grooved terrain. We map grooves on the USGS Voyager and Galileo Mosaic of Ganymede in order to unravel their spatial distribution and tectonic setting. A total of 14,707 grooves were identified, digitized and statistically analysed. A quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…We utilize the regional groove system map of light terrain (60°N–60°S) as presented by Rossi et al. (2020; Figure 3c). Similarly, to understand the structurally controlling factors on dark terrain, we utilize the global geological map as presented by Collins et al.…”
Section: Resultsmentioning
confidence: 99%
“…We utilize the regional groove system map of light terrain (60°N–60°S) as presented by Rossi et al. (2020; Figure 3c). Similarly, to understand the structurally controlling factors on dark terrain, we utilize the global geological map as presented by Collins et al.…”
Section: Resultsmentioning
confidence: 99%
“…We improved the regional scale groove mapping of Rossi et al (2020), where grooves were identified as topographic expression of trough structures whose bottom is identified by a contrast in brightness depending on the illumination conditions (Figure 9). First, the grooves detected by Rossi et al (2020) were mapped on the global image mosaic of Ganymede with a resolution of 1 km, assembled by the USGS Astrogeology Science Centre (Becker et al, 2001). The selected grooves from this data set and located in the Nippur Sulcus area were updated, improved and georeferenced to the new controlled 359 m/pixel global Ganymede mosaic from Voyager and Galileo images by Kersten et al (2021), allowing the detection of a larger number of features.…”
Section: Nippur Sulcus Grooves' Analysismentioning
confidence: 99%
“…First, the grooves detected by Rossi et al. (2020) were mapped on the global image mosaic of Ganymede with a resolution of 1 km, assembled by the USGS Astrogeology Science Centre (Becker et al., 2001). The selected grooves from this data set and located in the Nippur Sulcus area were updated, improved and georeferenced to the new controlled 359 m/pixel global Ganymede mosaic from Voyager and Galileo images by Kersten et al.…”
Section: Nippur Sulcus Grooves' Analysismentioning
confidence: 99%
See 2 more Smart Citations